Aerodynamic analysis of the asynchronous phenomenon of a impinging jet on a concave surface. Issue 10 (26th November 2019) - LeBlanc, Benoit; Poitras, Gérard J.; Brizzi, Laurent-Emmanuel; Roy, Gilles
ABSTRACT: The focus of this study is to numerically reproduce the asynchronous oscillations of an impinging slot jet on a concave surface experimental configuration. A Detached Eddy Simulation (DES) numerical simulation was realised at a Reynolds number of R e b = 6667 with respect to the slot jet width. The topological characteristics of the flow were also analyzed using the Proper Orthogonal Decomposition (POD) method. It was therefore possible to propose a sequence of flow topologies (four distinct flow states) during the changeover phenomenon of the impinging slot jet. The results show that the asynchronous phenomenon of the impinging slot jet seems to be related to the transitional characteristics of the jet flow. The flow topology of the most stable and energetic states (top and bottom jet flow states) creates a pressure imbalance inside the area of interest, resulting in the appearance of two transitional flow states. For the top or bottom impinging jet flow states, the jet remains in a relatively stationary position and the flow in the area of interest is quasi-two-dimensional. However, during the rapid changeover of the jet between these two states, small vortex structures prevail inside the area of interest for the centre jet states.